2010
DOI: 10.1111/j.1365-3156.2010.02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint: High susceptibility to Chikungunya virus of Aedes aegypti from the French West Indies and French Guiana

Abstract: Summary Objectives  To estimate the vector competence of Aedes aegypti populations sampled from distinct anthropogenic environments in French Guiana, Guadeloupe and Martinique for the strain CHIKV 06.21. Methods  F1/F2 females were orally infected at titres of 106 and 107.5 pfu/ml in blood‐meals. Disseminated infection rates (DIR) of mosquitoes were estimated using indirect fluorescent antibody assay on heads’ squashes, 7 or 14 days post‐infection (pi). Results  At a titre of 107.5 pfu/ml, DIR ranged from 88.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Ae. aegypti from the French West Indies and French Guiana, infected by blood with a titre of showed infection rates from 88.9% to 100%, but as low as 37.6–62% when infected with a titre of [58]. Girod et al found that infection rates were found to depend heavily on the housing density of the region where the mosquito was captured, with dense housing yielding an infection rate of 56.8% and diffuse housing a rate of 38.2%.…”
Section: Methodsmentioning
confidence: 99%
“…Ae. aegypti from the French West Indies and French Guiana, infected by blood with a titre of showed infection rates from 88.9% to 100%, but as low as 37.6–62% when infected with a titre of [58]. Girod et al found that infection rates were found to depend heavily on the housing density of the region where the mosquito was captured, with dense housing yielding an infection rate of 56.8% and diffuse housing a rate of 38.2%.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the establishment of CHIKV in temperate American countries is not simply a fiction, even if less than 30% of both mosquito species collected in the southern part of the United States (VRB from Florida) were able to transmit CHIKV_0621. It has been found that A. albopictus mosquitoes from Florida are more competent vectors of CHIKV than A. aegypti (31)(32)(33). Outbreaks of DENV, also transmitted by Aedes mosquitoes, have occurred in Texas and Florida in the past few years (46), reinforcing the risk of epidemics due to imported arboviruses in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Given the alarming epidemiological situation due to the very recent chikungunya outbreak affecting the Caribbean islands, the need for evaluation of the vector competence of American mosquito populations is compelling. Until now, studies were only limited to mosquitoes from the United States and the French Caribbean (31)(32)(33)(34). With the aim of understanding the factors that may influence CHIKV emergence in the Americas and the risk of a CHIKV epidemic spreading throughout the continent, we carried out a comprehensive Pan-American evaluation of vector competence of 35 A. aegypti and A. albopictus populations from 10 countries toward three CHIKV isolates belonging to two distinct lineages.…”
Section: Hikungunya Virus (Chikv) Is An Alphavirus In the Familymentioning
confidence: 99%
“…It circulated in an epidemic form in the urban area of Cayenne until May 2015 [5]. Locally, the only recognized mosquito vector of CHIKV is Aedes aegypti [6]. As there is no specific treatment or vaccine against CHIKV, the best prevention strategy is to limit exposure to mosquitoes through individual and collective protection measures.…”
Section: Background and Objectivesmentioning
confidence: 99%